Pemahaman Siswa Terhadap Bahan Ajar Muatan Lokal Upacara Tabot Bengkulu di Kelas V SDN 52 Kota Bengkulu - Camelia Gultom; Dwi Anggraini; Herman Lusa (Universitas Bengkulu, 2019)
This study aims to determine the ability of students to understand the teaching materials Local Content of Tabot Bengkulu ceremony in class V State Elementary School 52 Kota Bengkulu on 3 aspects of learning outcomes, namely academic skills (cognitive), attitude (affective), and psychomotor skills. The method used in this research is quantitative descriptive method with percentage technique. The sample in this research is the students of VB SDN 52 Bengkulu in the academic year 2016/2017 which is 25 students. The sample was determined by cluter random sampling technique in the population. The research instrument uses a test sheet. Data analysis technique is done by using learning result test that is adjusted to the value of KKM (Criteria Completed Minimum) subject of Local Content applicable in SDN 52 Kota Bengkulu, that is equal to 67. The result showed that the students of VB SDN 52 Kota Bengkulu have not been able to understand the material Ajar Local Content Tabot Bengkulu ceremony with an average of 73.33% and when viewed from the completeness of learning, students VB SDN 52 Bengkulu City has not been completed because based on the benchmark reference assessment students declared complete if the value is greater or equal to 67 as much as 75- 80%.